Advanced Control Systems : theory and applications - Kondratenko, Yuriy P. (River Publishers series in automation, control and robotics., 2021)
Advanced Control Systems: Theory and Applicationsprovides an overview of advanced research lines in control systems as well as in design, development and implementation methodologies for perspective control systems and their components in different areas of industrial and special applications.